Transformational leadership and job satisfaction in a Malaysian private sector company: a preliminary study - Zulkifly, Nurul Afiqah; Asyraf, Syed Amirul (Human Resource Management Academic Research Society, 2024)
Transformational leadership has emerged as one of the most prevalent leadership styles in today's organizational landscape. The manner in which a leader exercises their leadership style is closely linked to the job satisfaction experienced by employees. Nonetheless, there exists a notable gap in research concerning the transformational leadership style and its correlation with job satisfaction among employees in the private sector of Malaysia. Consequently, this study seeks to explore the impact of transformational leadership on employee job satisfaction within a private sector organization located in Serdang, Selangor, Malaysia. This research serves as an initial investigation that will be broadened to include additional factors that may affect job satisfaction. The data collected were analyzed using SPSS, and the preliminary results suggest that transformational leadership style has a significant positive effect on employee job satisfaction.